PENGARUH KEASLIAN PRODUK DAN PERSONAL BRANDING TERHADAP KEPERCAYAAN KONSUMEN DALAM MEMBELI PRODUK KECANTIKAN PADA PENGGUNA PLATFORM DIGITAL DI MANOKWARI - Lucia K. Rahaded; Sri Wahyuni; Febianus Heatubun (JURNAL LENTERA BISNIS, 2026)
Counterfeit beauty products circulating on digital platforms, coupled with weak personal branding among sellers, seriously undermine consumer trust in Manokwari. This study examines the partial and simultaneous effects of product authenticity and personal branding on consumer trust in online beauty product purchases. Drawing on Kotler and Keller's (2016) consumer trust theory, Schiffman and Wisenblit's (2015) product authenticity framework, and Rampersad's (2008) personal branding concept, a quantitative approach was applied to 70 purposively selected respondents who had purchased beauty products through digital platforms in Manokwari. Likert-scale questionnaire data were analysed with multiple linear regression using IBM SPSS. The results show that: (1) product authenticity has a positive and significant effect on consumer trust (β=0.312; t=3.287; sig=0.003); (2) personal branding has a positive and significant effect on consumer trust (β=0.421; t=4.518; sig=0.000); (3) both variables jointly exert a significant effect (F=18.742; sig=0.000) with R²=0.381. Personal branding emerges as the dominant predictor. These findings highlight the need for marketing strategies that integrate product authenticity guarantees with consistent digital reputation building.